2017
DOI: 10.1177/1069072717748956
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Reinforcement Sensitivity on Vocational Interest and Self-Efficacy

Abstract: Using the constructs of the behavioral activation system (BAS) and behavioral inhibition system (BIS), as defined by the reinforcement sensitivity theory of personality, the purpose of this study was to determine new linkages between personality traits and interest/self-efficacy across Holland’s hexagon. Specifically, it was proposed that (a) the BAS would positively relate to global liking of vocational interest and negatively relate to global disliking of interest; (b) the BAS would positively relate to ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
(275 reference statements)
1
6
0
1
Order By: Relevance
“…One study showed that reduced self-efficacy was related to increased levels of the BAS in high-school students with substance abuse [ 36 ]. However, Baker et al (2017) reported BAS positively related to self-efficacy in terms of social confidence and enterprising confidence among undergraduate students [ 87 ]. It may be that the relationship between two constructs could be influenced by various factors such as the type of self-efficacy or specificity of samples, and the findings of this study also might be affected by such factors.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that reduced self-efficacy was related to increased levels of the BAS in high-school students with substance abuse [ 36 ]. However, Baker et al (2017) reported BAS positively related to self-efficacy in terms of social confidence and enterprising confidence among undergraduate students [ 87 ]. It may be that the relationship between two constructs could be influenced by various factors such as the type of self-efficacy or specificity of samples, and the findings of this study also might be affected by such factors.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between self-efficacy and BAS was found previously [46][47][48][49]. Sherman et al [49] argued that self-efficacy plays a vital role in performing a wide range of health behaviors [71].…”
Section: Mediating Role Of Self-efficacy In the Association Between B...mentioning
confidence: 93%
“…Self-efficacy and BAS sensitivity are positively related to each other and to better performance [ 46 , 47 , 48 , 49 ]. Research indicates that self-efficacy is associated positively with BAS and sensitivity to reward [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations